Penerapan keadilan restoratif dan celah praktik korupsi (Integritas : Jurnal Antikorupsi, 2023)
This study aims to analyse the application of restorative justice as an alternative to punitive measures when settling criminal cases at the police level. It also seeks to identify potential forms of corruption in the application of restorative justice relating to criminal acts. This study uses socio-legal research with an emphasis on law implementation, particularly regarding  the handling of criminal cases by law enforcement agencies, especially the police. Police environment, especially in the East Java region; victims and perpetrators of crimes whose cases were resolved by a restorative justice mechanism, namely victims of cases of domestic violence, abuse, and theft; Community leaders involved in the process of settling cases with a restorative justice mechanism. To complete the interview, a Focus Group Discussion (FGD) was held involving academics, practitioners and civil society organisations, consisting of the Centre for Human Rights Law Studies, Kontras, LBH Surabaya, Indonesian Corruption Watch Malang, the Surabaya Children’s Crisis Centre, and legal professionals. The results of this study indicate that in practice there are a number of vulnerabilities to corruption that are not in line with the ideal values of restorative justice. The function of a mediator, carried out by investigators, is vulnerable to abuse due to the disharmony of arrangements, lack of oversight mechanisms, and the interests of the litigants. Corrupt behaviour arises through the "buying and selling" of cases, which can be resolved through the process of restorative justice. Victim-Offender Mediation and Family and Community Group Conference are restorative justice models which can be used.